Dipolar-Driven Formation of Cobalt Nanoparticle Chains in Polyethylene Films - Altbir-Drullinsky, D; Allende-Prieto, S; Casagrande-Denardin, J (Elsevier Ltd, 2015)
Abstract Using a simple method we produce polyethylene film with embedded chains of cobalt nanoparticles. The crystalline magnetic nanoparticles were synthesized through a simple chemical reduction method at room temperature using ultrasonic assistance. These particles were incorporated in a polyethylene matrix using a solution blending mechanism under an external magnetic field. The morphology and magnetic properties of Co nanoparticle aggregates were studied experimentally and by means of Monte Carlo simulations, showing a chain-like structures due to the strong dipolar interaction between aggregates. The hysteresis loops reveal typical ferromagnetic behavior at room temperature and magnetic anisotropy associated to a linear ordering of particles into the polymeric matrix. Numerical results confirmed the chain-like character of the aggregates and that an external magnetic field aligns them along its direction. The low-cost of the fabrication process of these polymeric magnetic films give them a strong potential for industrial and technological applications. © 2015 Elsevier B.V.